(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2016)
In the present work, several batches of indomethacin press coated tablets were prepared with drug and Avicel PH 102 utilizing the press coating technology. The core tablet was compression coated with minimal compression pressure. The compression coating mixture was formulated using various amount of lactose and xanthan gum which was used as the release retarding agent. Three formulations (IX-1, IX-2 and IX-3) were designed to evaluate the release profile as function of xanthan gum load. In vitro drug release testing demonstrated that the drug release was inversely proportional to the amount of xanthan gum in the coating formulations. In addition, formulation IX-2 was modified by incorporating hydroxypropyl methyl cellulose (HPMC) 15 cps into the compression coating formulation to understand their effects on drug release. The formulation was evaluated for its properties and correlated with in vitro and kinetic release studies. Incorporation of HPMC caused the highest fraction of drug to be released in the dissolution fluid. The physico-chemical properties of the excipients can be held responsible for the discrepancy in release rate of indomethacin. From kinetic analysis drug release was found to follow Higuchi mechanism for all the formulations. Overall, the study concluded that excipients present in the coating formulations make a significant impact on drug release. Dhaka Univ. J. Pharm. Sci. 14(2): 187-192, 2015 (December)